Mitochondrial dynamics: Orchestrating the journey to advanced age. (June 2015) - Biala, Agnieszka K.; Dhingra, Rimpy; Kirshenbaum, Lorrie A.
Abstract: Aging is a degenerative process that unfortunately is an inevitable part of life and risk factor for cardiovascular disease including heart failure. Among the several theories purported to explain the effects of age on cardiac dysfunction, the mitochondrion has emerged a central regulator of this process. Hence, it is not surprising that abnormalities in mitochondrial quality control including biogenesis and turnover have such detrimental effects on cardiac function. In fact mitochondria serve as a conduit for biological signals for apoptosis, necrosis and autophagy respectively. The removal of damaged mitochondria by autophagy/mitophagy is essential for mitochondrial quality control and cardiac homeostasis. Defects in mitochondrial dynamism fission/fusion events have been linked to cardiac senescence and heart failure. In this review we discuss the impact of aging on mitochondrial dynamics and senescence on cardiovascular health. This article is part of a Special Issue entitled: CV Aging. Highlights: Senescence contributes to mitochondrial dysfunction and heart failure. Mitochondrial dynamics are impaired by aging. Cardiac senescence disrupts mitochondrial clearance.